PENERAPAN ARSITEKTUR KONTEMPORER PADA BANGUNAN BANDUNG CREATIVE HUB - Farisulqisthi Mediawan; Yusvika Ratri Harmunisa (Jurnal Arsitektur ARCADE, 2024)
Abstract: The creative industry is the process of creating ideas, creativity and ideas that produce works or products. The creative hub or creative center is a place for creative industry activists to gather and develop their talents and creativity. Even though in Indonesia there are many buildings that function as creative centers, the question is to what extent these buildings are able to stimulate the creativity of creative industry players. One of the proposed solutions is to apply contemporary architectural design. This architecture is considered to be a way to stimulate the creativity of its users because it is not bound by time and always evolves with the times, in line with the spirit of creativity that is always advancing. Bandung Creative Hub was chosen as the focus of the research because it was considered successful in implementing contemporary architectural principles well. This research aims to understand the design form of a creative center that adopts contemporary architecture. The research method used is descriptive qualitative, by collecting data from various journals to describe this phenomenon. The research stages include data collection , analysis and drawing conclusions to provide a clearer picture of the influence of building design on the creativity of its users.Keyword: Bandung, Contemporary Architecture, Creative Center, Creative Industry.Abstrak: Industri kreatif merupakan proses penciptaan ide dan gagasan yang menghasilkan karya atau produk. Creative hub atau pusat kreatifitas merupakan tempat untuk mengembangkan dan menyalurkan kreativitas para pegiat industri kreatif. Di Indonesia, telah banyak didirikan bangunan-bangunan semacam itu, namun belum pasti apakah mereka sudah cukup efektif dalam memacu kreativitas. Salah satu solusi yang diusulkan adalah menerapkan arsitektur kontemporer, yang fleksibel dan selalu berubah mengikuti perkembangan zaman, mirip dengan kreativitas individu yang terus berkembang. Bandung Creative Hub menjadi objek penelitian karena dianggap menerapkan arsitektur kontemporer dengan baik. Penelitian ini bertujuan untuk mengevaluasi desain creative center yang menerapkan arsitektur kontemporer. Metode penelitian yang digunakan adalah metode kualitatif deskriptif, yang menggunakan data dari berbagai jurnal untuk menggambarkan fenomena yang ada. Tahapannya mencakup pengambilan dan pengumpulan data, analisis data, dan penarikan kesimpulan. Tujuan utamanya adalah untuk memahami bagaimana desain bangunan pusat kreatif dapat mempengaruhi kreativitas penggunanya, dengan harapan hasil penelitian ini dapat membantu pengembangan bangunan serupa di masa depan.Kata Kunci: Arsitektur Kontemporer, Bandung, Creative Center, Industri Kreatif